Tinjauan Kritis Urgensi Pembentukan Pengadilan Agraria : Upaya Menangani Inefektivitas Penyelesaian Konflik Agraria pada Peradilan Tata Usaha Negara dan Peradilan Umum - Ahmad Bilaldzy; Relys Sandi Ariani (Jurnal Hukum Lex Generalis, 2022)
Agrarian conflicts weakened the Administrative Judiciary and General Judiciary sectors in their settlement. The number of agrarian cases according to the Consortium for Agrarian Renewal for the period 2010-2019 amounted to 3,358 cases. The plantation, property, and infrastructure sectors become the largest agrarian conflicts in the last 5 years. Normative juridical research methods, statutory approaches and case studies, primary and secondary legal materials with analysis, and technical descriptive analysis. So the author analyzes the Urgency of the Establishment of Agrarian Courts. The results of the study assessed that judicial power is free without outside intervention. The type of court chamber has not been able to solve problems in the land sector properly. An Agrarian Court is needed in an effort to resolve land problems and reduce blur in the authority to file cases.